2015
DOI: 10.1007/s12035-015-9350-8
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin for Delirium Prevention: a Meta-analysis of Randomized Controlled Trials

Abstract: Recently, two high-quality clinical randomized controlled trials (RCTs) regarding the preventive effect of exogenous melatonin on delirium drew inconsistent conclusions. We therefore performed a systemic review to explore whether melatonin had a benefit on delirium prevention. MEDLINE, EMBASE, and Cochrane Library were searched from January 1980 to April 2015 for English language studies. After strict selection and evaluation, the data were extracted from the included four RCTs. The primary outcome of this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 53 publications
(80 reference statements)
1
49
1
1
Order By: Relevance
“…Studies have demonstrated that the administration of melatonin may improve the quality of sleep and prolong sleep time among ICU patients, while others have found that the prophylactic administration of low‐dose, exogenous melatonin may decrease the incidence of delirium . A meta‐analysis of randomized controlled trials of studies using exogenous melatonin for delirium prevention found that melatonin supplementation had a significant preventive effect in decreasing the incidence of delirium in medically ill older adults …”
Section: Substrates Of Deliriummentioning
confidence: 99%
“…Studies have demonstrated that the administration of melatonin may improve the quality of sleep and prolong sleep time among ICU patients, while others have found that the prophylactic administration of low‐dose, exogenous melatonin may decrease the incidence of delirium . A meta‐analysis of randomized controlled trials of studies using exogenous melatonin for delirium prevention found that melatonin supplementation had a significant preventive effect in decreasing the incidence of delirium in medically ill older adults …”
Section: Substrates Of Deliriummentioning
confidence: 99%
“…Melatonin is also disturbed after surgery, but did not reduce the incidence of POD in an older hip fracture population [80]. According to a metaanalysis, melatonin supplementation decreased the incidence of delirium in medical wards, but not in elderly surgical patients [81]. Statins were shown to have anti-inflammatory effects and may therefore prevent delirium.…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…According to the association between delirium and irregular patterns of melatonin secretion, which has been described by several studies, irregular melatonin secretion could be one of the mechanisms of delirium (10,23,30,31,(50)(51)(52) as well as the presence of sleep deprivation in hospitalized delirious patients at the ICU, as it has been indicated that melatonin and its agonists could be an effective supplement for prevention and management of delirium (38,53,54). Furthermore, several studies have reported the marked improvement of delirium in delirious patients without side effects due to the use of melatonin and ramelteon (6,45,46). According to the literature, pharmacological methods are not yet rec- ommended for prevention of delirium in critically ill patients, based on reviewed studies, especially because melatonin could improve patients' sleep; further trials could be performed to evaluate the efficacy of melatonin on prevention of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Delirium leads to an increase in the duration of mechanical ventilation, by interfering with weaning, increasing the time of stay at the ICU, and decrease of functional outcomes. It is also associated with disturbance in consciousness, change in cognition, disturbed psychomotor activity, and abnormal sleep-wake cycle (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%